The influence of communication skills and emotional quotient intelligence on employee performance through organizational citizenship behaviour - Andy, Andy; Fauzan, Rizky; Daud, Ilzar; Iman Kalis, Maria Chirstiana; Hendri, M. Irfani (Institute of Computer Science (IOCS), 2023)
Employee performance shows the extent to which employees achieve company expectations and goals. To achieve these goals, employee performance must be supported by qualified human resources. In achieving this goal, the intelligence quotient is used to measure performance, communication skills, and emotional quotient intelligence must be prioritized. The primary objective of this research is to investigate the impact of communication skills and emotional quotient intelligence on employee performance within the context of Indomaret in West Kalimantan. Furthermore, this study examines the potential mediating role of organizational citizenship behaviour in this relationship. The research employed structural equation modeling (SEM) as the primary methodology, utilizing the IBM AMOS 24 statistical software package. This research investigates the association between independent and dependent variables, incorporating mediating variables to provide empirical evidence for the formulated hypotheses. The data collection strategy employed in this study involved the distribution of a questionnaire to a sample of 200 employees from Indomaret in the West Kalimantan region who were selected as respondents. The results showed that communication skills and emotional quotient intelligence positively and significantly affected employee performance. Organizational citizenship behaviour also indicates a strong influence on employee performance. Meanwhile, organizational citizenship behaviour mediates between communication skills and emotional quotient intelligence on employee performance.